IMPLEMENTASI AKAD WADIAH DALAM PRODUK TABUNGAN DI BANK SYARIAH MANDIRI DAN TINJAUANNYA MENURUT HUKUM EKONOMI SYARIAH - Lulu Rodiyah; Abd Hadi (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACT Since Sharia Banking Law issued, Sharia bank is blooming and gaining the trust of people in Indonesia. This is showed by the increase of the number of the established Sharia bank in Indonesia. However, in their practice, these Sharia banks are not in accordance with Islamic law. They plagiarize usury principles from conventional bank and just translate it to Arabic language e.g. Sharia savings and Akad Wadiah.In principle, the foundation of this product is correct according to Fiqh due to its Wadiah base. However, in their implementation, Sharia bank may applies Wadiah Yad Dhamanah principle; whereas, Akad Wadiah Yad Dhamanah by name can’t be found in the classical Fiqh literature, and if this principle is further analyzed, two contradicting Akads which are forcibly combined will be found, i.e. Akad Wadiah and Akad Qard.This research is field research, where the researcher involved directly in the field or research object i.e. Bank Syariah Mandiri, Lamongan branch. The data is collected by observing and interviewing the management and the employee of Bank Syariah Mandiri, Lamongan branch, thus the collected data is the core of the research object which then analyzed using Qualitative Research method. The result shows that the application of Akad Wadiah in Bank Syariah Mandiri, Lamongan branch is using Wadiah Yad Dhamanah principle, which is not in accordance with the Sharia Economic Law. Keywords: implementation, Wadiah, Sharia Economic Law.